Kontribusi Kekuatan Otot Lengan Dan Daya Ledak Otot Tungkai Terhadap Kemampuan Renang Gaya Bebas 50 Meter - M Imran Hasanuddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
This research is a kind of quantitative descriptive research that uses a "correlational" research design. This study aims to find out: (1) Is there a contribu- tion of arm strength with a 50 meter freestyle ability to students in the study program in the field of the city, (2) Is there a contribu- tion of the limbs with a 50-meter freestyle ability to students in the study program in the new town. 3) Is there a contribution of strength with the weight of the limbs together with the ability of the 50-meter freestyle in the student study program in the new market area.The population is all students of the study program of education and training in the city of Bandung. The sample used was 30 students in the study program in the field of education in the city of Kotabaru, as many as 30 people. The sample determination technique is by random selection by means of a simple random sampling. The data analysis technique used was descriptive analysis and inferential analysis through the SPSS 22 program at a significance level of Î± 0.05.The results of the study indicate that; (1) Is there a contribu- tion of arm strength with a 50-meter freestyle ability to students of the study program in the new market, with a value (r) of 0.718 (Pvalue = 0.000 <Î± 0.05); (2) Is there a limb explosive superpower with 50 meter freestyle ability in the students of the study program in the new urban market, with a value (r) of 0.549 (Pvalue = 0.002 <Î± 0.05); and (3) Are there Kontribubsik arm strength and leg explosive power with 50 meter freestyle ability in the student study program in the city center, with a R value of 0.769 (Pvalue = 0.000 <Î± 0.05); and the calculated F value is 19,525 Keywords: arm strength, leg explosive power, freestyle swimming ability